2005
DOI: 10.1016/j.virol.2004.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of varicella zoster virus attenuation by evaluation of chimeric parent Oka/vaccine Oka recombinant viruses in skin xenografts in the SCIDhu mouse model

Abstract: Varicella-zoster virus (VZV) is the only human herpes virus for which a vaccine has been licensed. A clinical VZV isolate, designated the parent Oka (pOka) strain was passed in human and non-human fibroblasts to produce vaccine Oka (vOka). The pOka and vOka viruses exhibit similar infectivity in cultured cells but healthy susceptible individuals given vaccines derived from vOka rarely develop the cutaneous vesicular lesions characteristic of varicella. Inoculation of skin xenografts in the SCIDhu mouse model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
40
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 35 publications
8
40
0
Order By: Relevance
“…Thus, attenuation of V-Oka is not solely the result of mutational events clustered within IE 62 but may include reduced expression in VZV ORFs 65, 66, and 67 that together reduce assembly and spread of virus. Such a notion is supported by recent studies in which overlapping cosmid sets were used to generate recombinant VZV; chimeric VZV containing P-Oka-derived sequences covering ORFs 30 to 55 on a V-Oka background displayed wild-type infectivity in skin xenografts (34). Together, the data suggest that diminished vaccine virus virulence reflects a combination of mutations acting to reduce V-Oka replication.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, attenuation of V-Oka is not solely the result of mutational events clustered within IE 62 but may include reduced expression in VZV ORFs 65, 66, and 67 that together reduce assembly and spread of virus. Such a notion is supported by recent studies in which overlapping cosmid sets were used to generate recombinant VZV; chimeric VZV containing P-Oka-derived sequences covering ORFs 30 to 55 on a V-Oka background displayed wild-type infectivity in skin xenografts (34). Together, the data suggest that diminished vaccine virus virulence reflects a combination of mutations acting to reduce V-Oka replication.…”
Section: Discussionmentioning
confidence: 77%
“…Three observations suggest that the SNPs reported here may not be solely responsible for the ability of virus to replicate in the skin and that virus present in the skin is still highly attenuated. First, a study using chimeric viruses containing portions of the vaccine and parental Oka virus indicated that growth of the virus in human skin is caused by differences at multiple sites throughout the genome, especially in genes 30-55 (20). The VZV SNPs that differed between the vaccine rashes and the vaccine batches in the current study (1) were in genes 51 and 62 and between genes 61 and 62.…”
mentioning
confidence: 65%
“…The VZV SNPs that differed between the vaccine rashes and the vaccine batches in the current study (1) were in genes 51 and 62 and between genes 61 and 62. However, cloned vaccine virus was used in the study with the chimeras (20) so that it did not have the polymorphic features of the vaccine virus; at least one SNP (nucleotide 105,356) in the cloned virus had the parental sequence rather than the sequence that is more prevalent in vaccine batches. Second, because virus transmitted from rashes in vaccinees to secondary cases remains highly attenuated, the SNPs that are more highly represented in vaccine rashes than in vaccine batches, are not associated with increased virulence.…”
mentioning
confidence: 99%
“…Yet studies of IE62 promoter activity with constructs containing various mutations within IE62 have shown only modest deficits in function evaluated in vitro (5). Further, recombinant chimeric viruses made from cosmids consisting of parental and vaccine Oka segments have not defined specific ORF62 SNPs associated with altered replication in vitro (29,38). These experiments showed that chimeric viruses with various segments from vOka were attenuated, independently of ORF62.…”
Section: Discussionmentioning
confidence: 99%